Program benefitů pro zaměstnance jako motivační faktor - Zelyczová, Nela (2018)
The aim of this bachelor thesis is to find out, how much the employee benefits influence the motivation of the workers. In the theoretical part of the thesis are explained the theories of motivations and how they are used to improve the performance of the employee. Furthermore, are explained the forms of the wages and the most used employee benefits in the Czech republic in this theoretical part. The practical part of this theses is related to the research, which was made by the questionnare and the interview in the firm ACP Traductera a.s. Through the questionnare was explored the relation between the benefits and work. At the end of the bachelor theses are explained the results of the research and the evalutions of the fulfillment of the aim of the theses.